(untitled) (PAMPA, 2025)
In Uruguay, at the beginning of the 21st century, agricultural changes were generated with the arrival of the agribusiness model driven by soybean cultivation, generating changes in agricultural entrepreneurs and in their social environment. Thus, the main objective of this research is to understand the process of changes related to agricultural entrepreneurs, linked to the expansion of rainfed agriculture in Young-Uruguay between 2002 and 2019. Data from interviews conducted with agricultural entrepreneurs carried out in the area between 2017 and 2019 are taken as a corpus of analysis. It is concluded that the characteristics of the agribusiness model permeated the entrepreneurs who remained in the area producing, although this model was not adopted in the same way by the different enterprises analyzed.